2021
DOI: 10.1002/ls.1560
|View full text |Cite
|
Sign up to set email alerts
|

Improving of the tribological properties of attapulgite base grease with graphene

Abstract: With the rapid development of industry, individuals paid increasing demanding on the friction‐reducing and antiwear properties of lubricants under harsh service conditions. Here, the attapulgite base grease and attapulgite greases with grephene were successfully synthesised. The tribological behaviours of the greases were comparatively investigated using a SRV‐IV tribometer with the ball‐on‐disk configuration. The results show that the attapulgite grease with graphene presents better friction‐reducing and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…With the complexity of modern mechanical systems and the severe demands of application conditions, additives have become important factors in endowing and improving the lubrication performance of greases under harsh working conditions [10][11][12][13]. ZDDP is a typical multifunctional lubricating additive, which can play the triple role of antioxidation, antiwear and corrosion inhibition [14].…”
Section: Introductionmentioning
confidence: 99%
“…With the complexity of modern mechanical systems and the severe demands of application conditions, additives have become important factors in endowing and improving the lubrication performance of greases under harsh working conditions [10][11][12][13]. ZDDP is a typical multifunctional lubricating additive, which can play the triple role of antioxidation, antiwear and corrosion inhibition [14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a reduction in the friction coefficient by up to 60% was obtained after adding 1 wt.% graphene to a semi-solid lubricant [33]. Nan et al [34] investigated the effect of mixing different graphene percentages with attapulgite-based grease. They observed that graphene additions improve the tribological behavior of the base grease, especially at high loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Pal as a kind of non‐metallic additive, can enhance the lubrication. [ 18,36,39,40 ] In recent years, researches showed that adding other lubricating additives on the basis of Pal can further improve the lubrication effect. [ 41 ]…”
Section: Introductionmentioning
confidence: 99%
“…Pal as a kind of nonmetallic additive, can enhance the lubrication. [18,36,39,40] In recent years, researches showed that adding other lubricating additives on the basis of Pal can further improve the lubrication effect. [41] In this study, different concentrations of PEG and CS were dispersed into deionized water to optimize the best lubrication effect.…”
Section: Introductionmentioning
confidence: 99%